Is Ridge Cultivation Sustainable? A Case Study from the Haean Catchment, South Korea - Marianne Ruidisch; Sebastian Arnhold; Bernd Huwe; Christina Bogner (Applied and Environmental Soil Science)
Non-sustainable agricultural practices can alter the quality of soil and water. A sustainable soil management requires detailed understanding of how tillage affects soil quality, erosion, and leaching processes. Agricultural soils in the Haean catchment (South Korea) are susceptible to erosion by water during the monsoon. For years, erosion-induced losses have been compensated by spreading allochthonous sandy material on the fields. These anthropogenically modified soils are used for vegetable production, and crops are cultivated in ridges using plastic mulches. To evaluate whether the current practice of ridge cultivation is sustainable with regard to soil quality and soil and water conservation, we (i) analysed soil properties of topsoils and (ii) carried out dye tracer experiments. Our results show that the sandy topsoils have a very low soil organic matter content and a poor structure and lack soil burrowers. The artificial layering induced by spreading sandy material supported lateral downhill water flow. Ridge tillage and plastic mulching strongly increased surface runoff and soil erosion. We conclude that for this region a comprehensive management plan, which aims at long-term sustainable agriculture by protecting topsoils, increasing soil organic matter, and minimizing runoff and soil erosion, is mandatory for the future.